The Culture of Western Europe / The Nineteenth and Twentieth Centuries - Mosse George I (Rand Mcnally College Publishing Company, 1961)
Introduction: The Nineteenth Century: 1815-1870, From the Nineteenth to the Twentieth Century: 1870-1918, Index.
Introduction: The Nineteenth Century: 1815-1870, From the Nineteenth to the Twentieth Century: 1870-1918, Index.